Optimalisasi Website Dan Digital Marketing Untuk Peningkatan Produksi Dan Pemasaran UMKM Kilo Kalori - Kadek Surya Adi Saputra; Ayu Chrisniyanti; I Nyoman Dwi Arysna Mahendra; Ni Putu Sinta Puspita Rani; Fransiska Devita Aulia (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The rapid development of information technology has pushed Micro, Small, and Medium Enterprises (UMKM) to adapt by implementing digital marketing strategies. Kilo Kalori, a culinary-based MSME, faces several challenges in optimizing its website and utilizing digital marketing effectively. The main problems include limited knowledge of digital promotion, lack of quality promotional content, and suboptimal website management. This community service program aimed to provide solutions through training and mentoring in website management and the implementation of practical digital marketing strategies. The method consisted of three stages: planning, implementation, and evaluation, utilizing a participatory approach involving lecturers, students, and the business owner. The results indicated significant improvements in both the appearance and functionality of the website, as well as enhanced skills in creating promotional content and leveraging social media platforms for marketing. Evaluation results showed that 72% of respondents agreed that the optimized website met their expectations and was easy to use. Additionally, 94.7% of participants stated that the digital marketing training was useful and easy to understand. This program successfully improved Kilo Kalori’s digital capacity and may serve as a reference model for similar initiatives targeting other UMKM.